2009
DOI: 10.1123/jpah.6.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Physical Activity Among Lebanese Adults: A Cross-Sectional Study

Abstract: Background:This survey aims to assess the prevalence of physical activity among adult Lebanese, and to report the relationship between sociodemographic variables and physical activity behavior, highlighting the correlates discouraging people to carry out physical activity.Methods:A cross-sectional study using an anonymous self-reported questionnaire was conducted on 346 adults from four Lebanese districts. Demographic characteristics, physical activity, smoking status, alcohol consumption, and medical history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 24 publications
4
20
1
3
Order By: Relevance
“…Cross-sectional studies report mixed results concerning the relationship between marital status and PA, although it is often an inverse relationship, where married individuals are less physically active than those who are unmarried [43]. This study showed that, both in the urban site and overall, a higher proportion of single participants engaged in moderate-to-vigorous PA than those who were divorced or separated, and comparable results to these were reported by a study in Lebanon [44].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies report mixed results concerning the relationship between marital status and PA, although it is often an inverse relationship, where married individuals are less physically active than those who are unmarried [43]. This study showed that, both in the urban site and overall, a higher proportion of single participants engaged in moderate-to-vigorous PA than those who were divorced or separated, and comparable results to these were reported by a study in Lebanon [44].…”
Section: Discussionmentioning
confidence: 99%
“…Tohme and colleagues [21] estimated the prevalence rate of daily exercise for 30 minutes in a nationally representative sample of 2,125 subjects at 20.4%. A cross sectional study conducted among 346 adults 18 years and over selected from large stores across all governorates yielded a much higher estimate (55%) [22]. Findings from the WHO STEPwise surveys in countries of the MENA region also show a wide range of prevalence estimates of physical activity, varying between 13.2% and 78.4% [23].…”
Section: Discussionmentioning
confidence: 99%
“…Population studies have been conducted in developed and developing countries on physical activity and health-related factors among the elderly [14-18]. However, few published studies have specifically investigated physical activity level determinants, among older adults in Brazil [7,8,19,20].…”
Section: Introductionmentioning
confidence: 99%